Cholinesterase inhibitors may not benefit mild cognitive impairment and mild Alzheimer disease dementia - Han, Jee-young (Alzheimer Dis Assoc Disord, 2019)
INTRODUCTION: We investigated whether cholinesterase inhibitors (ChEIs) benefit cognitive outcomes in mild cognitive impairment (MCI) due to Alzheimer disease (AD) and in mild AD dementia. METHODS: Data from 2,242 individuals, clinically diagnosed with MCI due to AD (MCI-AD, Clinical Dementia Rating [CDR] = 0 or 0.5) or with mild AD dementia (ADdem, CDR= 0.5 or 1), were available from the National Alzheimer’s Coordinating Center’s (NACC) Uniform Data Set (UDS). General linear mixed models were used to examine the annual change in the CDR Sum Boxes (CDR-SB) and in neuropsychological performance. We compared slopes before and after ChEI initiation among ChEI users, and also compared change in scores of ChEI users versus non-users. RESULTS: Thirty-four percent of 944 MCI-AD and 72% of 1,298 ADdem participants were ChEI users. Cognitive decline was greater after ChEI initiation in MCI-AD and ADdem groups (e.g., MCI-AD, CDR-SB: 0.03 points/year before initiation; 0.61 points/year after initiation, p<0.0001). Both MCI-AD and ADdem groups had faster decline after ChEI initiation than non-users (e.g., MCI-AD, CDR-SB: 0.61 points/year, ChEI users; 0.24 points/year, non-users, p<0.0001). DISCUSSION: This study suggests that ChEI use may not improve the cognitive course in MCI-AD and mild ADdem.